2013
DOI: 10.1634/theoncologist.2013-0224
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dexamethasone-Induced Hiccup in Chemotherapy Patients by Methylprednisolone Rotation

Abstract: Background. Dexamethasone-induced hiccup (DIH) is an underrecognized symptom in patients with cancer, and little information is available about its treatment. The aims of this study were to investigate the feasibility of methylprednisolone rotation as treatment and to confirm the male predominance among those with cancer who experienced DIH during chemotherapy. Methods. Persons with cancer who experienced hiccups during chemotherapy treatment and who were receiving treatment with dexamethasone were presumed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
(25 reference statements)
3
27
0
3
Order By: Relevance
“…Under this assumption, we found that hiccups during chemotherapy could be controlled without losing antiemetic potential by replacing dexamethasone with methylprednisolone. 2,4 We also observed that the severity of hiccups was attenuated by readministration of dexamethasone. 4 The authors wrote in the case presentation that ''hiccups continued constantly for seven days with only a few hours of daily relief'' in the first cycle and lessened by about eight hours in the second cycle.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Under this assumption, we found that hiccups during chemotherapy could be controlled without losing antiemetic potential by replacing dexamethasone with methylprednisolone. 2,4 We also observed that the severity of hiccups was attenuated by readministration of dexamethasone. 4 The authors wrote in the case presentation that ''hiccups continued constantly for seven days with only a few hours of daily relief'' in the first cycle and lessened by about eight hours in the second cycle.…”
mentioning
confidence: 63%
“…2,4 We also observed that the severity of hiccups was attenuated by readministration of dexamethasone. 4 The authors wrote in the case presentation that ''hiccups continued constantly for seven days with only a few hours of daily relief'' in the first cycle and lessened by about eight hours in the second cycle. Based on our previous finding, it is possible that hiccup tolerance contributed to mitigation of the symptom over time.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Lee GW et al succeeded in decreasing the induction of hiccups by changing patient medication from the antiemetic drug dexamethasone to methylprednisolone [11]. Their study suggested that hiccups occurring due to chemotherapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that antiemetic drugs including steroid drugs when combined with anti-cancer drugs may increase the risk of hiccups. Lee GW et al succeeded in decreasing the induction of hiccups by changing patient medication from the antiemetic drug dexamethasone to methylprednisolone in a patient who developed hiccups as a result of a dexamethasone-containing chemotherapy regime [11]. They concluded that dexamethasone-induced hiccups may be controlled via steroid rotation.…”
Section: Introductionmentioning
confidence: 99%